O transporte coletivo por ônibus de Belo Horizonte: informação e subjetividade no trabalho - Geisa de Carvalho Silva Ferreira (2000)
This work introduces a reflection over the human beings emergency as a worker, through the interrelations among information, subjectivity and work, themes which could not be excluded from the economic, social and technological mechanisms and determinations of modern times. The public transportation sector of Belo Horizonte was taken as a base to talk about themes as life, quotidian, work, subjectivity and information in their theoretical, conceptual and methodological articulations. From the point of view of psychoanalysis and institutionalism, the differential element of this work was to think, in a broad way, about the relations among those themes as a subjectivity producer. Thus, it was possible to perceive in the workers speech how they establish their own understanding of questions surrounding them. The research approach used in this study was of qualitative nature, with interviews broaching requisite elements for the working process, inside the environment in which this work flows to the comprehension of the collective representation elaborated upon the driver, collector and the forwarding agent.